A crise funcional do estado contemporâneo: juízes-legisladores versus legisladores-juízes - Soares, Mirelle Monte (Universidade do Vale do Rio dos Sinos, 2015)
This essay discusses the functional crisis of the contemporary state, through a hermeutic-philosophical approach. First, will contextualize the state in which model it is now part of that crisis and this is the dissertation, then explain to one of its phases will show up: the functional crisis. As the intention is to remain exclusively in the crisis between legislature and judiciary, will prove that the judiciary effectively increased, due to now living in a welfare state and that, beyond this involuntary growth, he also began to occupy and usurping a function that was not constitutionally within its competence, becoming a true normative production. Once shown the action, will be discussing about the legislative reaction: its limits and possibilities. Finally, we will conclude that the state really is in crisis and that the traditional functions must take place in the new democratic scenario, even accepting the input and participation of new actors.
Keywords: Estado contemporâneo; Crise funcional; Judiciário; Legislativo; Diálogo institucional; Contemporary state; Functional crisis; Judiciary; Legislature; Institutional dialogue; ACCNPQ::Ciências Sociais Aplicadas::Direito